Designing augmentative and alternative communication systems with Aboriginal Australians: vocabulary representation, layout, and access. (2nd October 2022) - Amery, Rebecca; Wunungmurra, Julie Gungungbuy; Bukuḻatjpi, Gurimaŋu; Dikul Baker, Rachel; Gumbula, Farrah; Yunupingu, Elah; Raghavendra, Parimala; Barker, Ruth; Theodoros, Deborah; Amery, Howard; Massey, Libby; Lowell, Anne
Abstract: Yolŋu (Aboriginal Australians of northeast Arnhem Land) are interested in developing augmentative and alternative communication (AAC) systems in their own languages to support communication opportunities and participation for their family members living with Machado–Joseph disease. Designing AAC systems in Aboriginal languages requires consideration of unique linguistic and cultural elements. Participatory action research in strength-based communication contexts was carried out by Yolŋu and Balanda (the Yolŋu word for non-Aboriginal people) researchers working together through a collaborative intercultural process. Culturally responsive literacy, language, and AAC activities were used to develop four prototype Yolŋu AAC sytems for Yolŋu with varied literacy skills. Data were coded using gerunds to identify and focus on action in the data. Reflective and analytical collaborative, oral group discussions were used to identify key considerations and, ultimately, a Yolŋu metaphor for the research. Yolŋu language, culture and worldview impacted all aspects of prototype design and decision making. Salient considerations related to representation, organization, layout, and access, are presented. Clinical implications and future research considerations are outlined.